PENGARUH EMPLOYEE ENGAGEMENT DAN KOMITMEN ORGANISASI TERHADAP KINERJA PEGAWAI SEKRETARIAT DPRD KABUPATEN BOGOR - Firdaus, Muhamad Rifal; Fadili, Dadan Ahmad (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2025)
Introduction: The performance of employees at the Bogor Regency DPRD Secretariat can be influenced by many factors, among which are Employee Engagement and Organizational Commitment. Employees who feel connected to their work and are fully committed to their jobs can improve employee performance and facilitate the achievement of institutional goals Methods: The approach taken was descriptive and quantitative. To analyze the data, path analysis was used, supported by Microsoft Excel and SPSS. The total number of participants was 83. The main source of data came from questionnaires given to employees at the Bogor Regency DPRD Secretariat. Results: There is a very strong connection between Employee Engagement and Organizational Commitment, as shown by a coefficient of 0,815. Employee Engagement has a partial effect on Employee Performance, contributing 28%. Organizational Commitment has a bigger partial effect on Employee Performance, making up 58,6%. When both Employee Engagement and Organizational Commitment are considered together, they have a combined influence of 6, 9% on the performance of employees in the Bogor Regency DPRD Secretariat. The remaining 31,1% is due to other factors that were not studied in this research. Keywords: Employee Engagement, Organizational Commitment, Employee Performance